Representação política no Brasil: uma análise do perfil das mulheres eleitas à Câmara dos Deputados (1986-2011) - Reis, Cíntia de Oliveira Santiago dos (Universidade Federal de São Carlos, 2010)
The objective of this work is to analyze the politics career pattern of this federal Brazilian representative. The clipping that was made for this work is the period between 1986 and 2011, all six legislatures. For this work I went a lifting the politics participation of the woman and analyzed inform like time of office, politics party, ideology and projects. With this information, we look for to discover who are these women? Where do you come from? Why support and where going after the office first?
Keywords: Mulheres na política; Brasil - deputados federais; Recrutamento político; Carreira política; Mulheres; Carreira Política; Recrutamento; Reeleição; Woman; Politics career; Recruitment; Reelection; CIENCIAS HUMANAS::CIENCIA POLITICA